2011
DOI: 10.1038/ejhg.2011.121
|View full text |Cite
|
Sign up to set email alerts
|

Copy number variants and infantile spasms: evidence for abnormalities in ventral forebrain development and pathways of synaptic function

Abstract: Infantile spasms (ISS) are an epilepsy disorder frequently associated with severe developmental outcome and have diverse genetic etiologies. We ascertained 11 subjects with ISS and novel copy number variants (CNVs) and combined these with a new cohort with deletion 1p36 and ISS, and additional published patients with ISS and other chromosomal abnormalities. Using bioinformatics tools, we analyzed the gene content of these CNVs for enrichment in pathways of pathogenesis. Several important findings emerged. Firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
65
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(71 citation statements)
references
References 66 publications
4
65
0
2
Order By: Relevance
“…Large CNVs (typically >500 kb) have been consistently associated with disease (Sharp et al 2006;Sebat et al 2007;Xu et al 2008;Greenway et al 2009;Kirov et al 2009;Miller et al 2010;Cooper et al 2011;Paciorkowski et al 2011;Girirajan et al 2013), but similarly sized CNVs are not uncommon and are found at frequencies of 5%-10% in the healthy population (Itsara et al 2009). If the pathogenicity of a CNV is increased by perturbing multiple functionally related genes, then we would expect large CNVs in healthy individuals to avoid such clusters.…”
Section: Discussionmentioning
confidence: 99%
“…Large CNVs (typically >500 kb) have been consistently associated with disease (Sharp et al 2006;Sebat et al 2007;Xu et al 2008;Greenway et al 2009;Kirov et al 2009;Miller et al 2010;Cooper et al 2011;Paciorkowski et al 2011;Girirajan et al 2013), but similarly sized CNVs are not uncommon and are found at frequencies of 5%-10% in the healthy population (Itsara et al 2009). If the pathogenicity of a CNV is increased by perturbing multiple functionally related genes, then we would expect large CNVs in healthy individuals to avoid such clusters.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the observation of infantile spasms and other epilepsy phenotypes, we compared the brain expressed genes to the Arx conditional knockout transcriptome list [43] and genes in synapse development and function (GO:0045202 and children), as these pathways have recently been associated with infantile spasm pathogenesis [44]. Due to the observation of cerebellar malformations, we also compared the brain-expressed genes for relationships with genes involved in cerebellar development and function (GO:0021549 plus those extracted from expert reviews [45,46]).…”
Section: Bioinformatic Analysismentioning
confidence: 99%
“…6,8,31,32 Infantile spasms are associated with maternally inherited duplications of 15q11-q13, suggesting a role for GABAergic synapses and postsynaptic density in the etiology of Dup15q seizure semiology. 33 Idic (15) is characterized by developmental delay, severe epilepsy, moderate-to-severe intellectual disability, early central hypotonia, autistic behavior, absent or poor language (e.g., marked echolalia), and minor dysmorphic features (e.g., down-slanting palpebral fissures, epicanthal folds, low-set ears, "coarse" facial features, and hypopigmented areas of the skin). 29,30 Metabolic workup and intracranial magnetic resonance imaging (MRI) are typically normal and characterization of seizures is limited in prior studies, which describe early onset of treatment-refractory epilepsy evolving into a Lennox-Gastaut syndrome (LGS) phenotype.…”
mentioning
confidence: 99%